PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 46 GAJAH SAKTI KECAMATAN MANDAU KABUPATEN BENGKALIS - Dewi Santi Marlina; Zariul Antosa Antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low yield learning science students, this can be seen from the results of the fourth grade students studied 46 Elephants Way Elementary School, with an average value of 60.56 class. This study aims to improve learning outcomes IPA fourth grade students of SD Negeri 46 Elephants Way with Implementation of Cooperative Learning Model Numbered Heads Together (NHT). Design research is action research (PTK) with two cycles. Based on the analysis of research data after applying the type cooperative learning model Numbered Heads Together (NHT), the average percentage of first cycle teacher activity increased 68.74% 85.41% in the second cycle. The average percentage of student activity also increased, which is 54.16% in the first cycle increased to 79.16% in the second cycle. learning outcomes in basic score with the average value of 60.56 and the first cycle of students increased by an average value of 61.20 with an increasing percentage of classroom learning achievement of 1.2% and the percentage of students who complete 36%, and the second cycle increased again to an average of 74.80 with the percentage improvement class learning outcomes 18.18% and the percentage of students who complete 84%. These results show that the implementation of cooperative learning model Numbered Heads Together (NHT), can improve learning outcomes IPA fourth grade students of SD Negeri 46 Gajah Sakti. Key Words: Numbered Heads Together, learning outcomes IPA